Case Report: Management of a delayed type III hypersensitivity reaction with acute kidney injury in a dog after administration of human serum albumin with immunoadsorption - Sänger, Florian; Nagel, Fabian; Herges, Saskia; Weber, Karin; Dörfelt, René (Frontiers in Veterinary Science, 2025)
A six-year-old, intact male German Shepherd, weighing 43 kg, was presented with generalized edema formation and acute kidney injury due to a suspected delayed type III hypersensitivity reaction and vasculitis 2 weeks after the administration of human serum albumin (HSA). At presentation, the patient had a moderately reduced general condition, a heart rate of 96/min, rectal temperature of 37.0 °C, generalized edema, hematoma and petechiae on all limbs and the abdomen, and scleral hemorrhage. The initial blood work showed a moderate anemia, a severe azotemia, and a moderate hypoalbuminemia. Marked proteinuria with a urine protein-creatinine ratio (UPC) of 6.26 was present. The presence of anti-HSA antibodies was proven with an in-house ELISA. For treatment, immunoadsorption (IA) was performed with the TheraSorb® Ig Omni 1 adsorber, which was integrated in the LIFE 21® apheresis unit. Due to severe azotemia, an intermittent hemodialysis treatment with the dialysis platform Fresenius 4008 was performed after IA. Both treatments were repeated on the following day. A total plasma volume of 1.9 liters and 3.7 liters, respectively, was processed with IA. On the following days, creatinine concentration declined and the patient improved significantly. The patient was discharged after 10 days. UPC decreased to 0.82 and edema completely resolved. Two weeks after discharge, Creatinine, UPC and albumin were in the reference range. IA might be an additional therapeutic option for dogs with severe acute kidney injury due to a suspected delayed type III hypersensitivity reaction.